Conditions and consequences of education: Microeconometric analyses - Annika Barbara Bergbauer (ifo Institut - Leibniz-Institut für Wirtschaftsforschung an der Universität München, 2019)
This study was prepared by Annika B. Bergbauer while she was working at the Ifo Center for the Economics of Education. It was completed in March 2019 and accepted as a doctoral thesis by the Department of Economics at the University of Munich in July 2019. It consists of four self-contained chapters that empirically analyze educational economics. The first paper relates education measures to economic development. The following three papers contribute to the understanding of student performance focusing on standardized testing, teacher specialization, and political environments. Chapter 1 motivates the topic and puts the four papers into perspective of the re-search background. Chapter 2 assesses the importance of human capital for regional development in Sub-Saharan Africa. The findings suggest a stronger correlation of development with cognitive skills than with quantitative measures of human capital, such as years of schooling. Chapter 3 investigates the achievement impact of alternative uses of student assessments. In result, the expansion of standardized external comparisons associates with improvements in student achievement. The effect of schoolbased comparison is stronger in low-performing countries. In contrast, only internal testing without external comparison and internal teacher monitoring including inspectorates do not affect student achievement. Chapter 4 investigates how teacher specialization to a field of subjects during stud-ies affects student achievement. The chapter finds that teacher specialization does raise the academic achievement of boys, but not of girls. Chapter 5 examines the influence of European Union (EU) membership of Eastern European countries on student achievement. The findings suggest a positive and statistically significant correlation of EU membership and reading scores. – – Diese Studie wurde von Annika B. Bergbauer während ihrer Zeit am ifo Zentrum für Bildungsökonomik erstellt. Die Studie wurde im März 2019 fertiggestellt und im Juli 2019 als Promotionsschrift an der Volkswirtschaftlichen Fakultät der Universität München angenommen. Sie besteht aus vier eigenständigen Kapiteln, die mittels empirischer Methoden bildungsökonomische Fragestellungen erörtern. Das erste Papier verbindet Bildungsmaße mit ökonomischer Entwicklung. Die folgenden drei Papiere tragen zum Verständnis von Schülerleistungen bei mit einem Fokus auf standardisierte Tests, Spezialisierung von Lehrern und der politischen Umgebung. Kapitel 1 motiviert das Thema und ordnet die vier Papier in den Forschungshintergrund ein. Kapitel 2 betrachtet die Bedeutung von Humankapital für regionale Entwicklung in Subsahara-Afrika. Die Studienergebnisse suggerieren eine stärkere Korrelation von Entwicklung mit kognitiven Fähigkeiten als mit quantitativen Maßen von Humankapital wie die Anzahl der Schuljahre. Kapitel 3 untersucht den Einfluss von unterschiedlichen Verwendungen von Schülertests auf Schülerleistungen. Die Befunde zeigen, dass die Expansion von standardisierten Test zum externen Vergleich mit Verbesserungen in den Schülerleistungen einhergeht. Der Effekt ist größer in Ländern mit niedrigen Schülerleistungen. Demgegenüber sind interne Tests ohne externen Vergleich und interne Lehrerbeobachtung (wie Schulinspektoren) ohne Auswirkung auf die Schülerleistungen. Kapitel 4 erforscht wie die Spezialisierung von Lehrern auf ein Fächerfeld Schülerleistungen beeinflusst. Die Ergebnisse legen nahe, dass männliche Schüler von spezialisierten Lehrern profitieren, während kein Effekt auf die Leistung von Schülerinnen zu finden ist. Kapitel 5 untersucht den Einfluss einer Mitgliedschaft osteuropäischer Länder in der Europäischen Union (EU) auf Schülerleistungen. Die Befunde implizieren eine positive und statistisch signifikante Korrelation von EU-Mitgliedschaft und Leseleistung.
Keywords: I28; H52; L15; D82; P51; 330; education; PISA; assessments; accountability; testing; achievement; development; cognitive skills; human capital; nighttime light intensity; teachers; European Union; Sub-Saharan Africa; Germany; international